HUKUM PERKAWINAN BEDA AGAMA MENURUT PUTUSAN MK NO.71 PUU-XX 2022 - Fitri Mindari Handayani; Mohammad Saleh (Jurnal HUKUM BISNIS, 2023)
The diversity of religions and beliefs in Indonesia does not rule out the possibility of inter-religious marriages occurring. According to Article 35 and its explanation, as well as Article 37 paragraph (1) of Law Number 23 of 2006 concerning Population Administration which indirectly provides opportunities for interfaith marriages to occur. This type of research is Normative Legal Research by defining legal issues, collecting legal materials, studying legal issues based on the materials that have been collected, drawing conclusions in the form of arguments that answer legal issues. The conclusion from this study is that according to the law, interfaith marriages are invalid through a review of Law Number 1 of 1974 concerning Marriage, Compilation of Islamic Law and Islamic Law and Constitutional Court Decision Number 71/PUU-XX/2022.Keywords: interfaith marriage